Solving Schrödinger equation by meshless methods (2016)
ABSTRACT: In this paper we apply a numerical meshless scheme for solving one and two dimensional time independent Schrödinger equation by means of collocation method with Radial Basis Functions interpolants. In particular we approximate the solutions using multiquadrics. The method is tested with some of the well-known configurations of Schrödinger equation and compared with analytical solutions, showing a great accuracy and stability. We also provide some insight on how to use meshless algorithms for obtaining the eigenenergies and wavefunctions of one- and two-dimensional Schrodinger problems.